Description of Student Communication and Attention Patterns In Islamic Religious Education Learning - Rismawan; Aliyu Ibrahim Musaddad (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this research is to describe the pattern of communication and the attention of students in learning Islamic religious education. Methodology: The type of research used is quantitative research, the population in this study is students of Senior High School, the sample to be used in this study is determined by purposive sampling method, the instrument used is questionnaire and the data analysis techique is using statistic descriptive Main Findings: The results of this study are that student communication is more dominant, good and also the attention of students is also very good in the process of learning the Islamic religion Novelty/Originality of this study: The novelty of this research is to describe the communication skills and attention of students in the learning process of Islamic religion. Suggestions for further research are to find a link between communication skills and students' attention in the learning process so that it becomes even better.